Website-Based E-Commerce System Design and Build to Increase Online Sales at Funika Furniture - Jaka Abdul Jabar; Dian Anubhakti (PT Mattawang Mediatama Solution, 2022)
This study examines how the role of website-based e-commerce used can increase the online sale of the Funika furniture company. Descriptive research is research used by researchers in this study. Researchers describe facts, data and information obtained from literature studies such as books and journals to research results related to the research topic. In this study, it is explained that along with the development of technology and information, people's demands for convenience in all fields are getting bigger. One of them is the ease of making buying and selling transactions. The demands of this society encourage various individuals, groups and companies to innovate better in making it happen. The development of ICT greatly facilitates entrepreneurs to innovate in their efforts to conduct transactions and marketing online, namely through website-based e-commerce. Various advantages and benefits can be felt to the maximum if the application and utilization are made properly. For consumers, this site will greatly facilitate them in shopping and transacting without having to be limited by time and place. Meanwhile, for entrepreneurs and companies such as the furniture company Funika, this can be a great opportunity to develop their business by increasing online sales to increase company revenues and profits.